2011
DOI: 10.1375/jsc.6.2.152
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Evaluation of Knowledge of and Attitudes toward VA Smoking Cessation Services

Abstract: Introduction:The aim of this study was to assess Veterans' and primary care clinic staff's knowledge about, and experiences with, tobacco cessation services available through their Department of Veterans Affairs (VA) medical facility.Methods:Qualitative, semi-structured, in-depth interviews and surveys were conducted with 7 patients and 12 providers/clinic staff members at three VA primary care clinics serving large numbers of rural Veterans. Interviews were transcribed and coded for the- matic content.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…3,4 Both bupropion and nicotine replacement therapy have been found to be more effective than placebo or no treatment, 5,6 but they are ineffective in many cases. In fact, a meta-analysis of clinical trials found that bupropion and a nicotine patch result in abstinence in only 20% and 13% of participants, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Both bupropion and nicotine replacement therapy have been found to be more effective than placebo or no treatment, 5,6 but they are ineffective in many cases. In fact, a meta-analysis of clinical trials found that bupropion and a nicotine patch result in abstinence in only 20% and 13% of participants, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were age 19 years or older and currently smoking Ն10 cigarettes per day. Study exclusions included (1) pathologic condition of the ear; (2) pregnancy; (3) indwelling cardiac pacemaker or defibrillator; (4) actively psychotic, severe cognitive impairment, or current significant substance abuse disorder; and (5) currently receiving another intervention for smoking cessation.…”
Section: Recruitment and Eligibility Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Health care-associated factors including limited access to treatment also appear to contribute [ 3 , 4 ]. Being uninsured [ 4 , 5 ], infrequent visits to and/or lack of a personal physician [ 4 , 5 ], a lower likelihood of being counseled about tobacco use [ 6 ], and insufficient knowledge about available treatment resources also likely play a role [ 4 , 7 ]. Considering that approximately 5.3 million Veterans, representing 24 % of all Veterans living in the US, reside in rural areas [ 8 ], this represents a substantial group of individuals who are at increased risk for smoking-related health problems.…”
Section: Introductionmentioning
confidence: 99%
“…However, attendance at these VHA specialty smoking cessation clinics among all veterans is as low as 13% [12]. For rural veterans, the following extrinsic factors may negatively affect access to smoking cessation treatment: distance from health services, lack of health care follow-up, and lack of knowledge about smoking cessation resources [13, 14]. …”
Section: Introductionmentioning
confidence: 99%